Evaluation of onion cultivars as affected by bulb maturity and bulb characteristics of intermediate-day yellow onions in South Korea. Issue 5 (2nd September 2020) - Lee, Jongtae; Moon, Jin-Seong; Kim, Juyeon; Park, Gwi-Ok; Kwon, Jin-Hyeuk; Ha, In-Jong; Kwon, Young-Seok; Chang, Young-Ho
ABSTRACT: This study evaluated the performance of 55 intermediate-day onion cultivars ( Allium cepa L.) in southeastern Korea, and clustered the cultivars based on bulb maturity and marketable bulb yield (MBY). Days from transplanting to bulb initiation (DTB) ranged from 146 to 177. Fresh bulb weight (FBW) and MBY were lower in early or mid-maturing cultivars than in late-maturing ones. The cultivar 'Eomcheongnan' produced the greatest FBW and MBY in the mid-maturing cultivars. Of the late maturing cultivars, 'Art', 'K-star', 'Okkimaru', 'Cheonjujunggo', 'Worldstar', and 'Johwang' ranked for MBY with more than 73.0 Mg ha −1 . Only 10 late-maturing cultivars including 6 cultivars with more than 73.0 Mg ha −1, 'Dekanmaru', 'Newmars', 'Hanaro' and 'Strike' had a significantly greater than 4 cultivars ('Volve', 'SuperRich', 'Marathoner', and 'Gangwon 1 ho') with the lowest MBY, which might be due to difference in maturity too short with 14–26 April for bulb initiation, and 3–13 June for harvest. Higher air temperature and lower rainfall during bulb development stage did not affect days from transplanting to harvest (DTH), but negatively affected FBW. In 47 cultivars except for early and mid-maturing cultivars which started bulb initiation before 10 April, MBY was positively correlated with only DTH (R = 0.401) and FBW (R = 0.960). All the 55 cultivars were classified into 5 clusters, but there were close distances in clusters among late-maturing cultivars.